(3eOi aGYdjI bhGYO GdeSFhdjI GdeOfjI ddeMce h GdCWQGa ai GdJMcje GdJLGQi GdOhdi (B: s (3OQGSI ebGQfI (B/ s - (3CMeO eMeO YHOGdUGOb eMeOs; (3MSf YHOGdHGSW LejYis; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2016)
(3GdWHjYI GdeJejRg degeI GdeMce CKGQJ XdGdG ef GdZehV Mhd GdJcjja GdbGfhfi dWHjYI Jdc Gdegeg heOi LhGR JbQjQ eSFhdjI GdeMce ai MGdI GdNWC GdYeOi Ch GdNWC Gdegfi GdLSje(B: (3hai Xd EZaGd GdfU Ydi bhGYO JaUjdjI hefVHWI JMOO eSFhdjI GdeMce abO JYOOJ GdfXQjGJ Gdabgjg hENJdaJ ajeG HjfgG(B: (3ceG JVGQHJ GdCMcGe GdbVGFjI HTCf GdeSFhdjI PGJgG(B: (3hbO COi ZjGH GdfUhU GdbGfhfjI GdJi JbQQ eSFhdjI GdeMce Edi EYeGd GdbhGYO GdYGeI ddeSFhdjI GdeOfjI hGdJi KHJ YOe aGYdjJgG ai GdMGdGJ GdJi JJLGhR ajgG eSFhdjI GdeMce CMcGe GdeSFhdjI GdeOfjI(B: (3hbO EJLg GdHMK dJbQjQ fXGeG NGUG heJcGedG jfXe eSFhdjI GdeMce jJTGHg Edi MO cHjQ eY OYhi GdeNGUeI GdebQQI ai GdbVGA(B: (3dMeGjI GdeMce GdeLJgO GdfRjg hJhaQ dg fhYG ef GdMUGfg VO OYGhi GdeSFhdjI GdcjOjI ChJdc GdJi JSJfO Edi NWC HSjW Ch YGOi(B: (3hdMeGjI GdeJbGVjf ef GdCNWGA GdYeOjI Ch GdLSjeI GdJi JbY ef HYV GdeMcejfs
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdeOfj (B2016.s
(3HHdjhLQGajG(B: (3UaMGJ (B335-356.s
Keywords: (3GdeSFhdjI GdeOfjI ddeMces; (3GdJMcje GdJLGQi GdOhdis; (3bhGYO GdeSFhdjI GdeOfjI ddeMces; (3NUheI GdJMcje s; (3Jcjja GdYdGbI GdbGfhfjI GdJj JQHW GdeMce HGdCWQGa s; (3Mbhb GdeMces; (3SdWGJ GdeMces; (3YRd GdeMces; (3eNGUeI GdeMces; (3OYhi GdeNGUeI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs